Preparation method of hollow carbon nanopump and preparation method of drug carrier containing the same

By preparing and modifying hollow carbonaceous nanopump materials, the problems of insufficient internal space utilization of nanoparticles and uncontrollable material size and texture in the prior art are solved, efficient loading and delivery of different drugs are achieved, and its application potential in the field of biomedicine is expanded.

CN117105211BActive Publication Date: 2025-04-15ZHONGKE HUISHENG (BEIJING) PHARM TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311065759.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2025-04-15
Estimated Expiration
2043-08-23

AI Technical Summary

Technical Problem

In the prior art, the internal space of nanoparticles is filled with surfactant, and the drug loading is less. The size of the hollow carbon nanopump is single, which can only change the neck length of the hollow carbon material, the size adjustment space is limited, the texture and polarity are uncontrollable, and the drug is not loaded with this type of carrier material.

Method used

By preparing hollow carbonaceous nanopump materials, the reaction was carried out under conditions of 150°C-220°C by hydrothermal reaction method, and the material was surface modified to regulate the size, texture and polarity of the material, and loading the drug using pressure control conditions.

Benefits of technology

It has achieved efficient loading and delivery of different types of drugs, regulated the release rate and release amount of drugs, and expanded the application prospects of hollow carbonaceous nanopump materials in the biomedical field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117105211B_ABST
    Figure CN117105211B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a hollow carbon nanopump and a method for preparing a drug carrier containing the nanopump, comprising the following preparation steps: step 1, mixing anionic surfactant, nonionic surfactant and water to obtain solution I; mixing carbohydrates with water to obtain solution II; step 2, fully mixing solution I obtained in step 1 with solution II, and performing hydrothermal reaction for different lengths under the temperature condition of 150°C-220°C; step 3, after the reaction in step 2, cooling, filtering, washing and drying to obtain a hollow carbon nanopump material. The hollow carbon nanopump material overcomes the problem that the neck length of the material can only be changed at this stage, and the size, texture and polarity of the material cannot be regulated; the hollow carbon nanopump material based on structural modification is loaded with drugs. Pressure control and other technologies are used to load the material with drugs, thereby regulating the loading capacity and delivery efficiency of the carrier for drugs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of functional materials, in particular to a method for preparing a hollow carbon nanopump and a method for preparing a drug carrier comprising the nanopump. Background Art

[0002] With the development of nanomaterial synthesis technology, the design and manufacture of hollow nanoparticles have received great attention in both basic research and practical applications. Nanomaterials with hollow structures have unique advantages in device preparation, catalytic reaction, storage materials, biomedical materials, etc. due to their special properties such as cavity, light weight, low density, and high specific surface area. Therefore, they have broad application prospects in the fields of biotechnology, medicine, and preparations. Nanomaterials have a wide range of morphologies, such as bowl-shaped, asymmetric, and vase-shaped. Among them, the combination of the hollow structure and asymmetric structure of nanoparticles [Chen C, Wang H, Han C, et al. Asymmetric Flasklike Hollow Carbonaceous Nanoparticles Fabricatedby the Synergistic Interaction between Soft Template and Biomass. J Am Chem Soc. 2017; 139(7): 2657-2663. doi: 10.1021 / jacs.6b10841]. Bottle-shaped nanoparticles (hollow inside and with only one opening on the structural wall) have unique morphology and structural properties, making them ideal carriers for loading, encapsulating, releasing and delivering various therapeutic drugs in the field of biomedical applications [Qiu J, Xu J, Xia Y. Nanobottles for Controlled Release and Drug Delivery. Adv Healthc Mater. 2021; 10(4): e2000587. doi: 10.1002 / adhm.202000587].

[0003] In the existing technology for preparing bottle-shaped nanoparticle materials, only the neck length of the material can be changed. At the same time, since the internal space of the prepared nanoparticles is filled with surfactants, the drug loading is small, and the carrier material is not used to load the drug, and the loaded drug is not used in the preparation of related drugs. [Chen C, Wang H, Han C, et al. Asymmetric Flasklike Hollow Carbonaceous Nanoparticles Fabricated by the Synergistic Interaction between Soft Template and Biomass. J Am Chem Soc. 2017; 139 (7): 2657-2663. doi: 10.1021 / jacs.6b10841][Wang Yong, Chen Chunhong, Han Chuanlong, Deng Jiang. Preparation method of hollow carbon material and its products [P]. Zhejiang Province: CN106082160B, 2018-04-27.]

[0004] Therefore, this patent starts from the application of biology, medicine and preparation, and prepares nanoparticles that are more suitable for the application field of biomedicine - hollow carbon nanopumps. The size, texture and polarity of the material are regulated to meet the material's loading requirements for different types of drugs. Summary of the invention

[0005] Based on the actual needs of biology, medicine and preparations, and in view of the shortcomings of the prior art, the present invention provides a method for preparing a hollow carbon nanopump and a drug carrier containing the material, which solves the problems that the internal space of nanoparticles is filled with surfactants, the drug loading is small, the size of the hollow carbon nanopump is single, and only the neck length of the hollow carbon material can be changed, the size adjustment space is limited, the texture and polarity are uncontrollable, and the drug is not loaded using this type of carrier material, thereby providing more options for the loading of different types of drugs.

[0006] The present invention adopts the following technical solution: On the one hand, the present invention provides a method for preparing a hollow carbon nanopump, comprising the following preparation steps:

[0007] Step 1, mixing anionic surfactant, nonionic surfactant and water to obtain solution I; mixing carbohydrate and water to obtain solution II;

[0008] Step 2, the solution I obtained in step 1 is fully mixed with the solution II, and a hydrothermal reaction is carried out at a temperature of 150° C. to 220° C. for different lengths of time;

[0009] Step 3: After the reaction in step 2, the hollow carbon nanopump material is obtained by cooling, filtering, washing and drying.

[0010] Furthermore, the method further comprises step 4, i.e., modifying the hollow carbon nanopump material, dispersing the material obtained in step 3 in an organic solvent, centrifuging after ultrasonication, and drying to obtain the hollow carbon nanopump material after surface modification.

[0011] Furthermore, the reaction conditions of step 4 are as follows: the drug is loaded under the conditions of -1-1.2 kg / cm2 pressure and 100-300 rpm / min for 1-8 hours.

[0012] Furthermore, the method further comprises step 5, i.e. loading the hollow carbon nanopump material with drugs: dispersing the material obtained in step 4 in a drug solution, and loading the drug under pressure control conditions, and drying to obtain the hollow carbon nanopump material loaded with drugs.

[0013] Furthermore, the method further comprises step 6, namely, drug release of the hollow carbon nanopump material: according to the molecular weight of the drug, the drug-loaded material obtained in step 5 is placed in a dialysis bag, and the drug is released and detected under certain conditions in an oscillator.

[0014] Furthermore, the anionic surfactant is oleic acid and / or sodium oleate, and the nonionic surfactant is one or more of Tween 80, Tween 20, and polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123).

[0015] Furthermore, in step 1, the reaction time is 21h-60h.

[0016] Further, the material obtained in step 3 is dispersed in an organic solvent, ultrasonicated and centrifuged to obtain a structurally modified hollow carbon nanopump material; the organic solvent is an ethanol solution with a concentration of 50%-100%, the ultrasonic time is 60-120min, and the ultrasonic temperature is 20-40°C; the centrifugal speed is 4500-9500rpm / min, and the centrifugal time is 3-10min; the drying temperature is 50-100°C, and the drying time is 2-24h.

[0017] Furthermore, the conditions for drug release of the hollow carbon nanopump material are: release in a dialysis bag with MW 10000-14000, release speed of 75-150 rpm / min, release temperature of 20-37° C., and release time of 1-24 h.

[0018] Furthermore, the particle size of the hollow carbon nanopump is 100nm-20μm.

[0019] Furthermore, the hollow carbonaceous nanopumps have good stability in the zeta potential range of ±40-±60 and are pH-dependent.

[0020] Furthermore, the hollow carbon nanopump surfactants include anionic, nonionic and cationic surfactants.

[0021] Furthermore, the Young's modulus of the hollow carbon nanopump ranges from 1 MPa to 10 GPa.

[0022] Furthermore, the specific surface area of ​​the hollow carbon nanopump is in the range of 50-600 m 2 / g.

[0023] The present invention also provides a method for preparing a drug carrier comprising a hollow carbon nanopump, wherein the material is dispersed in a drug solution to be loaded, and the drug carrier is obtained by loading the drug under a pressure-controlled environment, wherein the pressure value of the environment is -1-1.2 kg / cm 2 , loading time is 1-8h.

[0024] Compared with the prior art, the present invention has the following characteristics and beneficial effects:

[0025] (1) The method for preparing the hollow carbon nanopump and the method for preparing the drug carrier containing the nanopump provided by the present invention overcome the problems that the current method can only change the neck length of the material but cannot regulate the size, texture and polarity of the material and has not applied it to drug loading.

[0026] (2) The present invention provides a method for preparing a hollow carbon nanopump and a method for preparing a drug carrier containing the nanopump, and performs drug loading. Pressure control and other technologies are used to load the material with drugs, thereby regulating the drug loading capacity and delivery efficiency of the carrier.

[0027] (3) Through characterization methods, the morphology, size, and related physical and chemical properties of the hollow carbon nanopumps were further clarified.

[0028] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The main purpose and other advantages of the present invention can be realized and obtained by the solutions particularly pointed out in the description and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a SEM image of the small-volume hollow carbon nanopump material prepared by using sodium oleate: Tween 80 in a mass ratio of 1:1.2, 160° C., and reacting for 21 hours according to the present invention.

[0030] Figure 2 This is a SEM image of the small-volume hollow carbon nanopump material prepared by using oleic acid: P123 mass ratio of 1:1.2, 160°C, and reaction for 21 hours according to the present invention.

[0031] Figure 3 This is a SEM image of the medium-volume hollow carbon nanopump material prepared by using sodium oleate: Tween 80 in a mass ratio of 1:3, 160° C., and reacting for 40 hours as described in the present invention.

[0032] Figure 4 This is a SEM image of the large-volume hollow carbon nanopump material prepared by using sodium oleate: Tween 80 mass ratio of 1:12.4, 160° C., and reaction for 21 hours according to the present invention.

[0033] Figure 5 This is a SEM image of a hollow carbon nanopump material with a rough surface prepared by using sodium oleate: Tween 80: P123 in a mass ratio of 1:0.6:0.6, 160° C., and reacting for 21 hours as described in the present invention.

[0034] Figure 6 This is a SEM image of the flexible hollow carbon nanopump material prepared by using sodium oleate: Tween 20 mass ratio of 1:12, 160° C., and reaction for 21 hours as described in the present invention.

[0035] Figure 7 This is the SEM image of the hollow carbon nanopump material with lipophilic interior before material modification.

[0036] Figure 8 This is the SEM image of the hollow carbon nanopump material with hydrophilic interior after material modification.

[0037] Fig. 9 This is a SEM image of the short-necked hollow carbon nanopump material prepared by using sodium oleate: P123 mass ratio of 1:1.2, 160° C., and reaction for 12 hours as described in the present invention.

[0038] Fig.10 This is a SEM image of the medium-long neck hollow carbon nanopump material prepared by using sodium oleate: P123 mass ratio of 1:1.2, 160°C, and reaction for 21 hours.

[0039] Fig.11 This is a SEM image of the long-necked hollow carbon nanopump material prepared by using sodium oleate: P123 mass ratio of 1:1.2, 160°C, and reaction for 24 hours as described in the present invention.

[0040] Fig.12 Release curves of metformin after loading hollow carbonaceous nanopump materials with different volumes.

[0041] Fig.13 Release curves of hollow carbonaceous nanopump materials with different neck lengths after loading with metformin. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0043] The present invention provides a method for structural modification of hollow carbon nanopump materials and a method for drug loading and release, and the specific implementation methods are as follows:

[0044] Step 1, anionic surfactants, which may include oleic acid and sodium oleate, and nonionic surfactants, which may include Tween 80, Tween 20, and P123, are mixed with water to obtain solution I; and carbohydrates are mixed with water to obtain solution II. The mass ratio of anionic surfactants and nonionic surfactants to water in solution I is in the range of 1:20-1:350;

[0045] The ratio of carbohydrate to water in solution II is in the range of 1:10-1:15; the mass ratio of anionic surfactant to nonionic surfactant is in the range of 1:1-1:15.

[0046] Among them, P123 is a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer.

[0047] Furthermore, when adjusting the material size, the anionic surfactant is oleic acid, the nonionic surfactant is P123, the mass ratio of oleic acid to P123 is 1:1.2, and the volume is small.

[0048] The anionic surfactant is sodium oleate, the nonionic surfactant is Tween 80, and the mass ratio of sodium oleate to Tween 80 is 1:1.2 for small volume; 1:3 for medium volume; and 1:12.4 for large volume.

[0049] When adjusting the texture of the material, a flexible material is prepared, the anionic surfactant is sodium oleate, the nonionic surfactant is Tween 20, and the mass ratio of sodium oleate to Tween 20 is 1:10; when adjusting the surface characteristics of the material, the anionic surfactant is sodium oleate, the nonionic surfactants are Tween 80 and P123, the mass ratio of sodium oleate: Tween 80: P123 is 1:0.6:0.6, and a material with a rough surface can be prepared. When preparing materials with different neck lengths, the anionic surfactant is sodium oleate, the nonionic surfactant is P123, and the mass ratio of sodium oleate to P123 is 1:1.2.

[0050] Step 2: fully mix the two solutions obtained in step 1, and perform a hydrothermal reaction at a temperature of 150-220° C., wherein the reaction time is 21 h to 60 h.

[0051] Step 3, washing the product obtained in step 2 with water. Filter the reaction solution system with a 0.45 μm water filter membrane, and wash with deionized water 4 times. Dry the filtered material at 50-100° C. for 2-24 hours to obtain a hollow carbon nanopump material.

[0052] Preferably, the drying temperature in step 3 is 50-60° C. and the drying time is 4-5 h.

[0053] Among them, the particle size of the hollow carbon nanopump is 100nm-20μm. The zeta potential range of the hollow carbon nanopump is ±40-±60, with good stability and pH dependence. The surfactants of the hollow carbon nanopump include: anionic, nonionic and cationic surfactants. The Young's modulus of the hollow carbon nanopump ranges from 1MPa to 10GPa. The specific surface area of ​​the hollow carbon nanopump is between 50-600m 2 / g.

[0054] Step 4, dispersing the material obtained in step 3 in an organic solvent, performing ultrasound and centrifugation, and obtaining a structurally modified hollow carbon nanopump material. The organic solvent is an ethanol solution with a concentration of 50%-100%, the ultrasound time is 60-120min, the ultrasound temperature is 20-40°C; the centrifugal speed is 4500-9500rpm / min, the centrifugal time is 3-10min; the drying temperature is 50-100°C, and the drying time is 2-24h.

[0055] Furthermore, the organic solvent is a 50% ethanol solution, the ultrasonic time is 60 min, the temperature is 40° C., the centrifugal speed is 7500 rpm / min, the time is 5 min, and the drying is performed at 60° C. for 4 h. The ratio of the hollow carbon nanopump to the 50% ethanol solution is 1 g:250 mL.

[0056] Step 5: Disperse the material obtained in step 4 in the drug solution at a temperature of -1-1.2 kg / cm 2 The drug is loaded under pressure and 100-300 rpm / min for 1-8 hours, and the hollow carbon nanopump material loaded with the drug is obtained after drying.

[0057] As a preferred embodiment, the vacuum pressure value is -1kg / cm 2 , the adsorption time is 5-8h, and the stirring speed is 200rpm / min.

[0058] Step 6, placing the drug-loaded material in step 5 into a dialysis bag with a molecular weight cutoff of MW 10000-14000 for release, with a release speed of 75-150 rpm / min, a release temperature of 20-37° C., and a release time of 1-24 h.

[0059] Furthermore, the molecular weight cut-off of the dialysis bag was MW 14000, and the release was performed at 75 rpm / min and 37°C for 1-5 h.

[0060] Example

[0061] Preparation method is as described above, adjusting the reactant dosage. Figure 1-Figure 6 As shown:

[0062] Figure 1 SEM image of small-volume hollow carbon nanopump material prepared using sodium oleate: Tween 80 mass ratio of 1:1.2, 160°C, and reaction for 21 hours. Figure 2 SEM image of small-volume hollow carbon nanopump material prepared using oleic acid: P123 mass ratio of 1:1.2, 160°C, and reaction time of 21h. Figure 3 SEM image of the medium-volume hollow carbon nanopump material prepared using sodium oleate: Tween 80 mass ratio of 1:3, 160°C, and reaction time of 40h. Figure 4 SEM image of large-volume hollow carbon nanopump material prepared using sodium oleate: Tween 80 mass ratio of 1:12.4, 160°C, and reaction time of 21h. Figure 5 SEM image of the rough-surfaced hollow carbon nanopump material prepared by using sodium oleate: Tween 80: P123 mass ratio of 1:0.6:0.6, 160°C, and reaction for 21h. Figure 6 This is the SEM image of the flexible hollow carbon nanopump material prepared using sodium oleate: Tween 20 mass ratio of 1:12, 160°C, and reaction for 21 hours.

[0063] By adjusting the mass ratio of sodium oleate: Tween 80\Tween 20, the morphology and size of the hollow carbon nanopump material can be effectively controlled.

[0064] Figure 7 and Figure 8 The following are the SEM images of the hollow carbon nanopump material with lipophilic interior and the SEM images of the hollow carbon nanopump material with hydrophilic interior before and after material modification. In terms of the surface modification of the hollow carbon nanopump material, SEM shows that the internal space of the hollow carbon nanopump material will be filled with a large amount of surfactant before modification, and the surfactant in its internal space can be effectively eluted after modification, and the effective loading volume inside the material can be expanded. The amount of modified material, the ratio of organic solvent to water, and the elution temperature and time are the main factors affecting the material modification effect. A low proportion of organic solvent will lead to incomplete material modification, that is, the surface surfactant in the internal space of the material is not completely removed. Too high a proportion of organic solvent and too long a reaction time will lead to unstable morphology and structure of the material.

[0065] In addition, the unmodified hollow carbon nanopump has a lipophilic surfactant in its internal space, which makes the material lipophilic and can be loaded with oil-soluble drugs, simplifying the preparation process of oil-soluble drugs and facilitating the loading, delivery and absorption of oil-soluble drugs. The hollow carbon nanopump material modified with organic solvents has hydrophilicity and is suitable for the loading, delivery and absorption of water-soluble drugs.

[0066] Fig. 9 This is the SEM image of the short-necked hollow carbon nanopump material prepared using a sodium oleate: P123 mass ratio of 1:1.2, 160°C, and a reaction time of 12 hours. Fig.10 This is the SEM image of the medium-long neck hollow carbon nanopump material prepared using a sodium oleate: P123 mass ratio of 1:1.2, 160°C, and reaction for 21 hours. Fig.11 This is a SEM image of the long-necked hollow carbon nanopump material prepared by using sodium oleate: P123 mass ratio of 1:1.2, 160°C, and reaction for 24 hours as described in the present invention.

[0067] By adjusting the duration of the hydrothermal reaction, the length of the neck of the hollow carbon nanopump material can be effectively controlled.

[0068] Performance after drug loading:

[0069] See also Fig.12 Release curves of metformin after loading hollow carbonaceous nanopump materials of different volumes.

[0070] Under the same release conditions, simple metformin is rapidly released and dissolved in the dissolution medium, and the release mass is the maximum mass at the beginning of release. Small-volume hollow carbon nanopump materials are prepared by sodium oleate: Tween 80 mass ratio of 1:1.2, 160℃, and reaction for 21h; medium-volume hollow carbon nanopump materials are prepared by sodium oleate: Tween 80 mass ratio of 1:3, 160℃, and reaction for 40h.

[0071] When the same mass of metformin is released, the release rate of metformin is delayed due to the intervention of the hollow carbon nanopump material. The time interval of the sustained release phase of metformin is 0-60min. In addition, the release rate and release mass of metformin by the small-volume hollow carbon nanopump material are lower than those of the medium-volume hollow carbon nanopump material. It can be seen that by adjusting the size of the material, the release rate and amount of the drug can be effectively controlled.

[0072] See also Fig.13 Release curves of metformin after loading hollow carbon nanopump materials with different neck lengths.

[0073] Under the same release conditions, simple metformin is rapidly released and dissolved in the dissolution medium, and the release mass is the maximum mass at the beginning of the release. The short-necked hollow carbon nanopump material is prepared by sodium oleate: P123 mass ratio of 1:1.2, 160℃, and reaction for 12h. The medium-long neck hollow carbon nanopump material is prepared by sodium oleate: P123 mass ratio of 1:1.2, 160℃, and reaction for 21h.

[0074] When the materials are loaded with the same mass of metformin and released, the release rate of metformin is delayed due to the intervention of the hollow carbon nanopump material. Among them, the release rate and mass of metformin by the short-necked hollow carbon nanopump material are lower than those by the medium-long-necked hollow carbon nanopump material. It can be seen that by adjusting the neck length of the material, the release rate and amount of the drug can be effectively controlled.

[0075] In terms of drug loading of hollow carbon nanopump materials, the stirring speed and pressure control during drug loading play an important role in drug loading of the material. During drug loading, stirring at an appropriate speed can make the drug evenly dispersed while increasing full contact with the material; through external pressure control, the drug can be fully loaded into the material cavity.

[0076] The specific drug loading process is: disperse the material in the drug solution to be loaded, and load it under pressure-controlled environment to obtain the carrier drug. The environmental pressure value is -1-1.2kg / cm 2 , loading time is 1-8h.

[0077] In terms of drug-carrying material release and application, it has a regulatory effect on drug release, that is, it reduces the drug release rate while prolonging the drug release time, thereby effectively achieving drug delivery and absorption.

[0078] In summary, in the method provided by the present invention, the ratio of anionic surfactant to nonionic surfactant determines the size, texture, surface characteristics and surface properties of the material. By adjusting the ratio of anionic surfactant to nonionic surfactant, the size of the material can be accurately adjusted to achieve different drug administration speeds and different dosages. In addition, the rigidity and flexibility of the material and the roughness and smoothness of the material surface can be effectively adjusted by adjusting the ratio of other reactants.

[0079] After the hydrothermal reaction of this method is completed, the separation and purification method of the product determines the purity of the material and the subsequent drug loading performance. The use of conventional medium-speed qualitative filter paper will cause problems such as filtration, which is not conducive to the effective collection of materials. The use of water-based filter membranes with appropriate pore sizes can not only quickly and effectively remove impurities, but also ensure a higher yield.

[0080] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that a technician familiar with the technical field can think of within the technical scope disclosed in the present invention should be covered within the protection scope of the present invention.

Claims

1. A short-necked hollow carbon nanopump for use as a drug carrier to slowly release metformin, characterized in that: The method comprises the following preparation steps: Step 1, mixing sodium oleate, P123 and water to obtain solution I, wherein the mass ratio of sodium oleate to P123 is 1:1.2; mixing carbohydrates with water to obtain solution II; P123 is a triblock copolymer of polyethylene oxide-polypropylene oxide-polyethylene oxide; Step 2, the solution I and solution II obtained in step 1 are fully mixed, and a hydrothermal reaction is carried out at 160° C. for 12 h; Step 3: After the reaction in step 2, the short-necked hollow carbon nanopump material is obtained through cooling, suction filtration, washing and drying.

2. Use of a short-necked hollow carbon nanopump as claimed in claim 1 as a drug carrier for slowly releasing metformin, characterized in that: It also includes drug loading conditions: dispersing the material in the drug solution to be loaded, and loading the drug under pressure-controlled environment to obtain a carrier drug with an ambient pressure value of -1-1.2 kg / cm 2 , and the drug was loaded at 100-300 rpm / min for 1-8 h.

3. Use of a short-necked hollow carbon nanopump as claimed in claim 1 as a drug carrier for slowly releasing metformin, characterized in that: The release conditions of metformin are as follows: release in a dialysis bag with MW 10000-14000, a release speed of 75-150 rpm / min, a release temperature of 20-37°C, and a release time of 1-24 h.

Citation Information

Patent Citations

  • Preparation method for hollow carbon material and product

    CN106082160A

  • Preparation method of hollow carbon bowl powder

    CN109553082A

  • Flask structure carbon nanomaterial and preparation method thereof

    CN113104836A

  • Hollow fiber medicine carrier and its preparing method and use

    CN1586623A